Remarkable lives: Clare Campbell in conversation with Jerome Carson. Issue 1 (14th March 2016) - Campbell, Clare; Carson, Jerome
Abstract : Purpose: – The purpose of this paper is to provide a profile of Clare Campbell. Design/methodology/approach: – Clare provides a short autobiographical account of her life. Clare is then interviewed by Jerome and describes the life enhancing impact of creativity in her own life. Findings: – Clare describes her work initially with Wild Woman workshops and then Big Love Sista. Research limitations/implications: – Big Love Sista started when some 40 women all came and painted self-portraits in Clare's house, which led to an exhibition of 100 life sized portraits on women in recovery from difficult life events. Practical implications: – Apart from the healing power of Art, Clare's work shows the power of bringing leaders together with disadvantaged groups, using the medium of the circle to provide unique experiential change. Social implications: – Community leaders have access to lots of resources and opportunities. In coming together with disadvantaged groups, they can serve as role models, but equally they can be inspired by those they encounter in the medium of the circle. Originality/value: – Clare and those colleagues she has worked with over the years has shown the power of community and the transformative effects of groupwork. Few individuals can have had such a dramatic effect on so many people.